2012
DOI: 10.1016/j.jpainsymman.2011.12.277
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity, Spirituality, and End-of-Life Planning: A Single-Site Survey of Medical Inpatients

Abstract: Context Prior studies suggest that terminally ill patients who use religious coping are less likely to have advance directives and more likely to opt for heroic end-of-life measures. Yet, no study to date has examined whether end-of-life practices are associated with measures of religiosity and spirituality. Objectives To assess the relationship between general measures of patient religiosity and spirituality and patients’ preferences for care at the end of life. Methods We examined data from the Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 33 publications
(52 reference statements)
1
32
0
1
Order By: Relevance
“…This is consistent with prior research (e.g., Balboni et al, 2007;Caralis, Davis, Wright, & Marcial, 1993;Fischer et al, 2012;Hopp & Duffy, 2000;Johnson et al, 2008;Karches et al, 2012;Kwak & Haley, 2005;Smith et al, 2008;True et al, 2005), and the current study found this effect of ethnicity to be robust even after controlling for other personal characteristics such education, marital status, satisfaction with finances, and perceived health. Although not the primary focus of the present study, this suggests that sociocultural, familial, or relational aspects that could foster these differential views and behaviors are important to consider, and sensitivity to these factors is warranted when discussing EOL issues, particularly for health care providers, ministerial professionals, and those in the legal profession.…”
Section: Methodssupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with prior research (e.g., Balboni et al, 2007;Caralis, Davis, Wright, & Marcial, 1993;Fischer et al, 2012;Hopp & Duffy, 2000;Johnson et al, 2008;Karches et al, 2012;Kwak & Haley, 2005;Smith et al, 2008;True et al, 2005), and the current study found this effect of ethnicity to be robust even after controlling for other personal characteristics such education, marital status, satisfaction with finances, and perceived health. Although not the primary focus of the present study, this suggests that sociocultural, familial, or relational aspects that could foster these differential views and behaviors are important to consider, and sensitivity to these factors is warranted when discussing EOL issues, particularly for health care providers, ministerial professionals, and those in the legal profession.…”
Section: Methodssupporting
confidence: 92%
“…A number of studies have observed that ethnicity is related to views and behaviors involving end-oflife issues (e.g., Balboni et al, 2007;Fischer, Sauaia, Min, & Kutner, 2012;Johnson, Kuchibhatla, & Tulsky, 2008;Karches, Chung, Arora, Meltzer, & Curlin, 2012;Smith et al, 2008;True et al, 2005). Kwak and Haley (2005), in their review of 33 empirical studies, observed that non-White individuals were less likely than White persons to support advance directives, and that African American individuals consistently favored the use of life support.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The protestant patients were older than catholic patients, but still remain an independent factor in the multivariate analyses. A previous study showed no association between religious characteristics and DNACPR order [32]. However, other publications showed that religious individuals more frequently want aggressive measures to extend life [33,34], but these studies did not make any differences between religions.…”
Section: Determinants Of Dnacprmentioning
confidence: 69%
“…Some have suggested that religious doctrine, participation in a religious community, support from a higher power, a belief in miracles or the belief that do not resuscitate (DNR) is morally wrong may be reasons that religion is associated with choosing more aggressive treatment or wanting cardiopulmonary resuscitation (CPR) 9 11–13. Karches et al ,14 however, suggest that not all dimensions of religion may be associated with more aggressive treatment, and that prior studies used different measures of religion including religious affiliation, religiosity or religiousness and religious coping to assess these relationships. Geros-Willfond et al 15 also note the diversity in perspectives around religion and surrogate decision-making, suggesting that there are complexities around the ways in which religion and/or spirituality may shape preferences, decisions and assent around end-of-life treatment.…”
Section: Introductionmentioning
confidence: 99%